2017
DOI: 10.1210/jc.2017-00990
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Improvement of Glycemia in Prediabetes by Different Diagnostic Criteria

Abstract: Context:The effects of physical activity (PA) on improvement of glycemia may differ between prediabetic individuals defined by oral glucose tolerance test vs glycated hemoglobin (HbA1c).Objective:We studied the association between PA and improvement of glycemia in individuals with prediabetes defined by glucose vs HbA1c criteria.Design, Setting, and Participants:From the Whitehall II study, 957 participants with prediabetes defined by isolated impaired fasting glucose (i-IFG), isolated impaired glucose toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
8
17
0
2
Order By: Relevance
“…We observed an association between TLEE and prediabetes/diabetes development among women with a good glycaemic control. Differences in food patterns between men and women are common , and we have previously observed sex‐specific associations between lifestyle factors and glucose regulation in the Whitehall II cohort , supporting these findings. Whether late evening food consumption disturbs circadian rhythm differently in men and women needs further investigation.…”
Section: Discussionsupporting
confidence: 77%
“…We observed an association between TLEE and prediabetes/diabetes development among women with a good glycaemic control. Differences in food patterns between men and women are common , and we have previously observed sex‐specific associations between lifestyle factors and glucose regulation in the Whitehall II cohort , supporting these findings. Whether late evening food consumption disturbs circadian rhythm differently in men and women needs further investigation.…”
Section: Discussionsupporting
confidence: 77%
“…However, a recent study showed that HbA 1c may not be able to capture the pathophysiological diversity of impaired fasting glycemia (IFG) and impaired glucose tolerance (IGT) (2). Also, individuals identified as having prediabetes on the basis of the HbA 1c criterion seem to have a different response to physical activity and lower probability of reverting to normoglycemia than those identified through the use of the glucose criteria (3). Thus, understanding the pathophysiological differences between subgroups of individuals with prediabetes is crucial to stratify risk and to facilitate more targeted prevention-focused interventions.…”
mentioning
confidence: 99%
“…Adjusted for age, sex, smoking status, physical activity, and alcohol consumption 3. Adjusted for age, sex, smoking status, physical activity, alcohol consumption, and BMI.…”
mentioning
confidence: 99%
“…Despite there are prior studies evaluating the proportion of reversion to normoglycaemia, all them were heterogeneous in design, duration of follow-up and criteria definition yielding a broad range of reversion rates [15][16][17][18][19], and only few did it according to prediabetes status criteria [10,20]. The latter, a Japanese study [20] using four prediabetes subgroups according to elevated HbA1c and/or IFG, observed a greater proportion of reversion rates among those with elevated HbA1c levels.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…For example, some studies have found a better response to glucose regulation after applying lifestyle modifications only in individuals with IGT [9]. In addition, a recent study observed how individuals with HbA1c levels in range of prediabetes were less likely to revert to normal glycaemia after physical activity recommendations [10].…”
Section: Introductionmentioning
confidence: 99%